Potret Perempuan pada Film Cinderella (2015) dan Cinderella (2021): Sebuah Kajian Sastra Bandingan - Laily Raff Firdausy (Universitas Pendidikan Indonesia, 2023)
Cinderella is a well-known literature which tells the story of a girl who suffers from living with her mother and stepsisters, then finds love and happiness by meeting the prince. This romance story filled with magic, loved by various groups, and thanks to its popularity, this story has been adapted several times for the big screen. Each story adaptation certainly has differences. This also applies to the film